Male postabdomen reveals ancestral traits of Megasecoptera among winged insects - Prokop, Jakub; Pecharová, Martina; Sinitshenkova, Nina D; Klass, Klaus-Dieter (Arthropod structure & development, 2020)
External male genitalia of insects are greatly diverse in form and frequently used in evolutionary context and taxonomy. Therefore, our proper recognition of homologous structures among various groups from Paleozoic and extant insect taxa is of crucial interest, allowing to understand the key steps in insect evolution. Here, we reveal structural details of two Late Carboniferous representatives of Megasecoptera (families Bardohymenidae and Brodiopteridae), such as the presence of separated coxal plates VIII and ventral expansions of coxal lobes IX. Together with the confirmed presence of abdominal styli in some other members of Palaeodictyopterida (Diaphanopterodea) this suggests that early pterygotes may have had traits more archaic than expected. Whether or not these traits point to a stem-group relationship of Palaeodictyopterida to all other Pterygota as suspected by earlier authors remains unclear at this stage. Furthermore, the present study provides an updated comparison of male postabdomen morphology among extant species of wingless Archaeognatha and representatives of early diverging groups of Pterygota from the Late Carboniferous and Early Permian, the Megasecoptera (Palaeodictyopterida), Permoplectoptera (Ephemeroptera) and Meganisoptera (Odonatoptera).
Keywords: Pterygota; Male genitalia; Fossils; Animals; Biological Evolution; Abdomen; Insecta; Male; Palaeodictyopterida; Comparative morphology; mužské pohlaví; biologická evoluce; Archaeognatha; zkameněliny; hmyz; zvířata; břicho